Researches on Damage Identification in Passive Vibro-Isolation Devices - A. Leopa; S. Nastac; C. Debeleac (Shock and Vibration)
This paper deals with the theoretical aspects combined with experimental analysis regarding early damage identification in passive vibro-isolation devices. Basically, this research presents the relevant results obtained for a singular element. Rubber based on elements is discussed especially. This study was a naturally fall-back of the authors large analysis regarding the dynamic behaviour of the passive isolation devices against vibration, shocks and seismic waves. Main hypothesis supposed that on the exploitation time, all technical devices and systems acquire different levels of wearing because of the dynamic overloads and their derivative influences (aging, fatigue, energy dissipation, external heating or cooling, etc.). Hereby the performance characteristics changes and the system becomes working improperly. Numerical simulations were developed for simple spatial configuration of isolation device. Stochastic approach of essential results was briefly presented nearby the relevant results and discussions.